2015
DOI: 10.1371/journal.pone.0139205
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electrostatic Interactions in Binding of Histone H3K4me2/3 to the Sgf29 Tandem Tudor Domain

Abstract: Several reader domain proteins that specifically recognize methyllysine-containing histones contain the negatively-charged aspartate or glutamate residues as part of the aromatic cage. Herein, we report thermodynamic analyses for the recognition of histone H3K4me3 and H3K4me2 by the tandem tudor domain of Sgf29 and its recognition site variants. Small uncharged and large aromatic substitutions on the Asp266 site resulted in a significant decrease in binding affinities for both H3K4me3 and H3K4me2, demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…This modification led to increased specificity towards H3K9me3, and 3.5-fold weaker binding to H3K9me2, emphasizing the importance of electrostatic interactions and hydrogen bonding in mediating selectivity towards Kme2 readout. Similar results were obtained in studies that modified D266 through site-directed mutagenesis in SGF29′s Tudor domain while also demonstrating the importance the negative charge in providing structural integrity of the reader domain complex [ 130 ].…”
Section: Reading Kme3supporting
confidence: 80%
See 1 more Smart Citation
“…This modification led to increased specificity towards H3K9me3, and 3.5-fold weaker binding to H3K9me2, emphasizing the importance of electrostatic interactions and hydrogen bonding in mediating selectivity towards Kme2 readout. Similar results were obtained in studies that modified D266 through site-directed mutagenesis in SGF29′s Tudor domain while also demonstrating the importance the negative charge in providing structural integrity of the reader domain complex [ 130 ].…”
Section: Reading Kme3supporting
confidence: 80%
“…Tudor domains are characterized by a singular or tandem five-stranded β-barrel domain that mediates the recruitment of the histone tail to the groove within the barrel. Recruitment of the histone tail leads to insertion of Kme2/3 or methylated arginine residues into an aromatic cage ( Figure 15 b) [ 130 , 131 ]. Tudor domains can be distinguished as three forms: single Tudor, tandem Tudor, and hybrid Tudor domains.…”
Section: Reading Kme3mentioning
confidence: 99%
“…A similar result was observed for the Sfg29 tandem tudor domain bound to H3 K4Me2/3. 53 This is the opposite of the observation in the HP1 chromodomain. Thus, it appears that the contribution of salt bridges and electrostatic interactions is dependent on the nature of the binding pocket.…”
Section: ■ Protein Recognition Of Methylated Lysmentioning
confidence: 77%
“…24,27 Additional investigations into the binding sites of both proteins concluded that the histidine in DIDO1 is necessary for pH dependent recognition of H3K4me3, 26 and the aspartic acid in the equivalent position in TAF3 forms important hydrogen bonds with the H3T6 side chain and a water molecule near the cage. 27,[50][51][52] In both systems, there are signicant NMR chemical shi perturbations of Met upon binding H3K4me3, 24,27 suggesting Met makes key contacts with the PTM. Mutation of Met to Ala resulted in loss of binding, however no additional mutational analysis has been conducted to further investigate its role.…”
Section: Mutational Strategies In Model Phd Domains Dido1 and Taf3mentioning
confidence: 99%